TINGKAT BERPIKIR GEOMETRI VAN HIELE DITINJAU DARI PERBEDAAN GENDER DAN KEMAMPUAN MATEMATIKA - Sofia Sa’o; Finsensius Yesekiel Naja; Agustina Mei (Jurnal Dedikasi Pendidikan, 2020)
The purpose of this study is to determine the level of student thinking based on gender differences by exploring students 'geometrical thinking abilities and creating learning examples to improve students' level of thinking. While the differences in mathematical abilities are high, medium and low mathematical abilities. This type of research is exploratory research using a naturalistic qualitative approach, by taking 3 male students and 3 female students as research subjects which are then grouped based on mathematical abilities. The results of each activity are analyzed and the level of thinking of each research subject is determined. All subjects still ignored class inclusion of quadrilateral shapes even though they were able to distinguish geometric shapes based on the properties of the components. the sequence of learning phases revealed by van Hiele, namely: (1) Information Phase (Information), (2) Guided Orientation Phase, (3) Explicitation Phase, (4) Free Orientation Phase Orientation), and (5) Integration Phase. The results obtained are that both male and female students are at the level of thinking 1. It is different from the difference in students' level of thinking when viewed from their mathematical abilities. For students who are in the high and medium grades, all students are at level 1 thinking, whereas in the low value group only one student is at level 1 thinking and the others are at level 0 thinking. While the learning examples made are Learning Implementation Plans (RPP) and Student Worksheets (LKS) are made with the hope of increasing the level of van Hiele students' geometry thinking from level 1 to level 2.